Simple Financial Recording Training Using Excel For Vocational School Students - Putra, Danang Adi; Midiastuty, Pratana Puspa; Suranta, Eddy; Indriani, Rini; Robinson, Robinson (Universitas Dehasen Bengkulu, 2025)
This training aims to improve the financial recording skills of Vocational High School (SMK) students through the use of Microsoft Excel as a practical tool. The problem that is often faced by vocational school students, especially majoring in accounting or business, is the lack of understanding and skills in conducting financial recording systematically and efficiently. In this activity, participants were trained starting from the introduction of the basic functions of Excel, the creation of simple financial report formats, to the use of basic formulas such as SUM, IF, and VLOOKUP to support basic accounting processes. This training was carried out in the form of an interactive workshop for two days with lecture methods, hands-on practice, and discussion. The results of the evaluation showed an increase in students' understanding and skills in compiling daily and monthly financial reports using Excel. This activity also encourages students to be better prepared to face the needs of the world of work, especially in the fields of administration and finance. With a hands-on approach, this training has a positive impact on the mastery of basic technology and accounting for vocational school students.